A risk assessment proposal for underground cavities in Hard Soils-Soft Rocks - Margherita, Zimbardo; Claudio, Cannone; Laura, Ercoli; Alessandra, Nocilla (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2018)
Underground calcarenite quarries in Marsala (Sicily) have been involved in a number of collapses that have, seriously damaged numerous buildings. The stability conditions were therefore examined in order to assess risk conditions within the historical centre of the town and the surrounding areas, which are subject to urban expansion. Starting with an extensive collection of historical information, the research was carried out through surveys of the cavities, systematic sampling of material, petrographic analysis and geotechnical testing. The results of laboratory tests and in situ investigations provided a geotechnical characterization of both the intact material and the rock mass. Correlating the deformability, yielding and strength parameters of the intact rock to the structural features, it was possible to define the range of variability of the shear strength parameters of the rock mass. The geotechnical parameters obtained were then introduced in the three-dimensional finite element codes and the stability and safety conditions of underground quarries were evaluated. Once the geometrical conditions of the single cavity (in its own location relative to the surrounding environment) were defined by means of a new parameter K, the safety factor was defined according to the intact rock and the rock mass strength and deformation modulus using the proposed abacuses. Solutions provide risk charts that allow the quantification of the hazard due to the presence of cavities adjacent in the subsoil. The applicability of the Abacus was investigated through an analysis of a real existing geometry in which collapse is not yet occurred and through a back analysis process on already collapsed underground cavities in three sites. Risk charts can be considered as a useful starting tool to be used in order to optimize the planning of specific surveys.